1990
DOI: 10.1051/gse:19900205
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to experimental infections with Haemonchus contortus in Romanov sheep

Abstract: Summary -Responses to immunization with aggregated human serum albumin (HSA) and to repeated experimental infections with H contortus were studied in 51 female lambs of the Romanov breed, born from 8 sires and 36 dams. The 8 sires were of haemoglobin genotype Hb AB; the 51 lambs were distributed into 3 groups of 17 each, corresponding to the 3 genotypes HbAA, HbAB and HbBB. In addition the experimental lambs were typed for antigens of the major histocompatibility system (OL./1). The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
2
1
Order By: Relevance
“…1998). However, this relationship has not been confirmed by other studies ( Luffau et al. 1990; amongst others).…”
Section: Discussioncontrasting
confidence: 59%
“…1998). However, this relationship has not been confirmed by other studies ( Luffau et al. 1990; amongst others).…”
Section: Discussioncontrasting
confidence: 59%
“…Some of these studies have been summarized in Table 7 . Polymorphisms within the ovine MHC complex were associated with resistance to T. colubriformis ( Douch and Outteridge, 1989 ), T. circumcincta ( Schwaiger et al, 1995 ), and H. contortus ( Luffau et al, 1990 ; Outteridge et al, 1996 ). However, Cooper et al (1989) , Blattman et al (1993) and Hulme et al (1993) did not find evidence of an association between polymorphisms in the ovine MHC locus and resistance or susceptibility to H. contortus .…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the pattern of egg excretion were probably due to the fenbendazole treatment. Benitez-Usher et al [5] and Luffau et al [22] have shown that thiabendazole treatment prevents the expression of immunity acquired by previous contact with Haemonchus contortus. Cabaj et al [8] also found changes in the immune system of sheep that had been drenched with fenbendazole.…”
Section: Discussionmentioning
confidence: 99%